Activation of the hypothalamic-pituitary-adrenal (HPA) axis contributes to the immunosuppression of mice infected with Angiostrongylus cantonensis. Issue 1 (December 2016) - Chen, Ai-ling; Sun, Xi; Wang, Wei; Liu, Jin-feng; Zeng, Xin; Qiu, Jing-fan; Liu, Xin-jian; Wang, Yong
Abstract Background Immunosuppression has been described as a consequence of brain injury and infection by different mechanisms.Angiostrongylus cantonensis can cause injury to the central nervous system and eosinophilic meningitis to human. Both T cell and B cell immunity play an essential role in the resistance of the infection. However, whether brain injury caused byA. cantonensis infection can lead to immunosuppression is not clear. Therefore, the present study sought to observe the alteration of immune responses in mice infected withA. cantonensis . Methods Mice were infected with 20 third-stageA. cantonensis larvae. The messenger RNA (mRNA) expression of inflammatory mediators in brain tissues was observed by qRT-PCR. Cell surface markers including CD3, CD4, CD8, CD19, B220, 7-AAD, annexin-V, IgM, AA4.1, and CD23 were evaluated by using flow cytometry. The immune functions of T and B lymphocytes were detected upon stimulation by ConA and antibody responses to a nonself antigen OVA, respectively. Activation of the hypothalamic-pituitary-adrenal axis was evaluated by analyzing the concentration of plasma corticosterone and levels of mRNA for corticotropin-releasing hormone, tyrosine hydroxylase, and c-fos. Results A. cantonensis infection results in obvious immunosuppression evidenced as progressive spleen and thymus atrophy and significant decrease in the number of lymphocyte subsets including B cells, CD3+ T cells, CD4+ T cells, and CD8+ T cells, as well as reduced T cell proliferation at 21 days post-infection and antibody reaction to exogenous protein after infection. However, the sharp decrease of splenic and thymic cells was not due to cell apoptosis but to B cell genesis cessation and impairing thymocyte development. In addition, helminthicide treatment with albendazole on infected mice at 7 days post-infection could prevent immunosuppressive symptoms. Importantly, infected mice displayed hypothalamic-pituitary-adrenal axis activation, with peak responses occurring at 16 days post-infection, and glucocorticoid receptor antagonist could partially restore the infection-induced cessation of B cell genesis. Conclusions Brain injury caused byA. cantonensis infection, like that of brain stroke and trauma, enhanced endogenous corticosteroid activity, resulting in peripheral immunosuppression.